Aspectos reprodutivos de Melipona compressipes fasciculata Smith. (Hymenoptera, Apidae ): Alimento larval, ovo e povoamento de colméias - Carvalho, Georgiana Eurides Viana de (2007)
For the State of the Maranhão, the Melipona compressipes fasciculata (Tiúba) possess a great importance, therefore servant, representing one of the main sources of income for diverse families is the social bee more, and possess ecological importance for the conservation of its natural ecosystems. Thus this research had as objective the determination of characters related to the larval food and to the weight of the egg, beyond to establish a process of settlement of colonies of Melipona compressipes fasciculata. For determination of the weight, density, average bulk of the larval food and the average weight of the egg had been evaluated nine colonies of where if it collected 520 cells of creates just-constructed, in a total of 520 eggs, 260 cells of create for attainment of the weight of the larval food and 260 cells of create for the attainment of the density. The collected data had been evaluated statistics. For the process of populate of beehives aiming at the multiplication of colonies through the rational division had been used adult, young the old bees and placed mass of cells of create spring in the same instant of the division, distributed in three treatments, constituted of 80, 160 and 240 adult bees, respectively, with 05 colonies each. Colonies had been selected strong mothers to be givers of the mass of cells of create springs and others to be givers of adult bees for the populate of the new colonies. This method of division was evaluated through the accompaniment of the weight of the formed colonies, as well as the amount of pots of food, presence of the virgin queen and of the fisiogástrica queen, amount of cells of creates constructed and so great of the mass of cells. With relation to the larval food it was gotten, average weight of 192, 9127 mg, mean density of 1,1728 mg/µl and 164,4890 µl average of bulk. For the weight of the egg the gotten average was of 2,8066 mg. With relation to the formed colonies, the colonies that had received 160 adult bees had been upper to excessively how much to the weight and the number of food pots, already the colonies that had received 240 adult bees had been upper to excessively how much to the frame number of it creates constructed. The colonies mothers had influenced the formed colonies how much to its genetic potential and they had not weakened after the withdrawal of the adult bees and of the mass of cells of it creates spring. Soon, is possible to carry through the populate of colonies of Melipona compressipes fasciculata through the based rational division in the number of adult, young the old bees , and mass of cells of create spring. The job of this method for the breeder will be helping to keep the genetic and productive potential of the colonies, as well as guaranteeing the maintenance of the woods diversity and the ecological balance for terrestrial ecosystems, being then basic for the search of the sustentabilidade of this activity inside of the State of the Maranhão.